2015
DOI: 10.3906/sag-1405-87
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive dysfunction and Alzheimer disease

Abstract: IntroductionThere are many comorbid diseases that become more common with ageing (1). Alzheimer disease (AD), which was described by Alois Alzheimer in 1907, is the most common form of progressive, irreversible dementia in the elderly (1-3). It affects more than 25 million people worldwide; without a major therapeutic breakthrough, its prevalence is expected to increase more than 100 million by 2050 (1-5).Worldwide, 200 million patients undergo surgery under anesthesia each year. As overall life expectancy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…It is thought that not only anesthetic agents, but also neurotoxicity, infl ammation, stress, intraoperative factors (e.g. hypotension, hypoglycemia) or the type of surgery have a role in the development of POCD (1,27). However, in recent researches there was an increasing concern that volatile anesthetics may impair cognitive functions over a long period of time, especially in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is thought that not only anesthetic agents, but also neurotoxicity, infl ammation, stress, intraoperative factors (e.g. hypotension, hypoglycemia) or the type of surgery have a role in the development of POCD (1,27). However, in recent researches there was an increasing concern that volatile anesthetics may impair cognitive functions over a long period of time, especially in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent researches there was an increasing concern that volatile anesthetics may impair cognitive functions over a long period of time, especially in older patients. Research showed that volatile anesthetics could increase amyloid peptide (Aβ) production and neurotoxicity, which are important pathological changes in AD development (1,11,12). Therefore, anesthesia and surgery are assumed as the risk factors that accelerate the onset of AD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations